The value of chest radiograph and computed tomography in pulmonary sarcoidosis - Greco, Francesca Gabriella; Spagnolo, Paolo; Muri, Margherita; Paladini, Ilaria; Chizzolini, Francesco; Piciucchi, Sara; Colombi, Davide; Sverzellati, Nicola (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Imaging makes a significant contribution to the diagnosis, prognosis and follow-up in sarcoidosis. Despite its increasing use, the role of computed tomography (CT) scanning in patients with known or suspected pulmonary sarcoidosis is still undefined. This review aims to compare the utility and limitations of chest radiograph and CT in patients with pulmonary sarcoidosis, with regards to the most critical clinical issues such as the diagnostic sensitivity, the differential diagnosis, and the prediction of the disease reversibility.